Persepsi Masyarakat Terhadap Ruang Terbuka Hijau Di Kecamatan Singkil Kota Manado - Talumepa, Reformator Anafero; Benu, Olfie Liesje Suzana; Lumingkewas, Jelly R.D. (AGRI-SOSIOEKONOMI, 2023)
This study aims to determine the public's perception of the existence and benefits of the environment given green open space, in order to support comfort, beauty, and support sustainability in Singkil District, Manado City. This research was conducted from April to July 2022. The data used in this study were primary data and secondary data. Primary data was obtained from interviews with the community using a questionnaire, while secondary data was obtained from government documents from the Singkil District. With the number of respondents as many as 27, namely 3 respondents in 9 villages in the Singkil District, the sampling technique used was purposive sampling. The data analysis used in this research is descriptive analysis. Based on the results of this study, it shows that the community needs the existence of green open space because it is useful and has a function for the community itself to reduce pollution and organize the spatial layout of the area. The existence of green open space in Singkil sub-district is still limited to a program from the government that has not been realized properly, because it has not been structured properly due to the dense population.